2017
DOI: 10.1002/term.2321
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive coating of decellularized vascular grafts with a temperature-sensitive VEGF-conjugated hydrogel accelerates autologous endothelialization in vivo

Abstract: No ideal small-diameter vascular graft for widespread clinical application has yet been developed and current approaches still suffer from graft failure because of thrombosis or degeneration. Decellularized vascular grafts are a promising strategy as they preserve native vessel architecture while eliminating cell-based antigens and allow for autologous recellularization. In the present study, a functional in vivo rodent aortic transplantation model was used in order to evaluate the benefit of bioactive coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Thus, there has been a corresponding increase in the study of decellularized tissue modification to enhance endothelialization and reduce thrombogenicity. In attempts to accelerate endothelialization, researchers have coated decellularized grafts with VEGF, VEGF hydrogels, integrin ligands, and cell adhesion peptides [1923]. Other groups have chosen to focus on decreasing graft thrombogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there has been a corresponding increase in the study of decellularized tissue modification to enhance endothelialization and reduce thrombogenicity. In attempts to accelerate endothelialization, researchers have coated decellularized grafts with VEGF, VEGF hydrogels, integrin ligands, and cell adhesion peptides [1923]. Other groups have chosen to focus on decreasing graft thrombogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…76,78,204,206,207 Studies that include the use of coated small diameter vessel ECM scaffolds in vivo reported high patency rates (patency rate) over periods of 3 (83%-xenograft) and 8 (100%-allograft) weeks and 2 (90%-allograft) and 3 (83%-xenograft) months (Table 3). 76,78,204,205 In all cases, scaffolds demonstrated robust smooth muscle and EC recellularization. 76,78,204,205 Finally, the combination of barrier and cell modulating compounds resulted in reduced production of blood coagulation factor in vitro, as well as reduced platelet accumulation and fibrin deposition in vivo.…”
Section: Small Diameter Ecm Scaffold For Coronary Artery Bypass Graftmentioning
confidence: 85%
“…76,78,204,205 In all cases, scaffolds demonstrated robust smooth muscle and EC recellularization. 76,78,204,205 Finally, the combination of barrier and cell modulating compounds resulted in reduced production of blood coagulation factor in vitro, as well as reduced platelet accumulation and fibrin deposition in vivo. 69 High in vivo patency rates and high cell presence suggest that scaffold coating may serve as a solution to achieving rapid EC repopulation of ECM scaffolds.…”
Section: Small Diameter Ecm Scaffold For Coronary Artery Bypass Graftmentioning
confidence: 85%
See 2 more Smart Citations